1970
DOI: 10.13057/biodiv/d040102
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymorphism at locus-2 of growth hormone gene of Madura cattle

Abstract: The objectives of the research were to detect DNA polymorphism at locus 2 of bovine growth hormone gene of Madura cattle and to know its genetic diversity. DNA polymorphisms and their effect on phenotypic traits have been studied widely in dairy cattle but not for beef cattle, especially for Indonesian local cattle. Polymorphism was detected using PCR-RFLP using primer GH-5 and GH-6 for amplifying locus 2 of growth hormone gene. Genetic diversity was analyzed based on the formula of Nei (1973, 1975). DNA polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…This was evident that the frequencies of allele and genotype of GH gene in the four exons of Pesisir cattle having value less than 0.99 except in exon 2 which was monomorphic. GH gene polymorphism was found in samples of Madura cattle was consistent with the results of research of Purwoko et al (2003), which stated that there were polymorphisms in the GH gene locus 2 which was positioned at 329 bp. About Katingan cattle, the results of the study found that there were variations in frequencies alleles namely polymorphic in exon 1, 2, 4 and 5, except exon 3 which was monomorphic.…”
Section: Frequencies Of Genotype and Allele Gh Genesupporting
confidence: 89%
“…This was evident that the frequencies of allele and genotype of GH gene in the four exons of Pesisir cattle having value less than 0.99 except in exon 2 which was monomorphic. GH gene polymorphism was found in samples of Madura cattle was consistent with the results of research of Purwoko et al (2003), which stated that there were polymorphisms in the GH gene locus 2 which was positioned at 329 bp. About Katingan cattle, the results of the study found that there were variations in frequencies alleles namely polymorphic in exon 1, 2, 4 and 5, except exon 3 which was monomorphic.…”
Section: Frequencies Of Genotype and Allele Gh Genesupporting
confidence: 89%
“…The study of GH gene MspI locus of Indonesian beef cattle have been reported in Ongole crossbred cattle (Sutarno et al, 2005;Sutarno, 2010), Madura cattle (Purwoko et al, 2003), Pesisir cattle (Jakaria et al, 2007), Bali cattle (Jakaria et al, 2009) and Grati dairy cows (Maylinda, 2011). Their studies indicated that polymorphism was found on Ongole crossbred cattle, Madura cattle, Pesisir cattle and Grati dairy cows.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship of genotype variations in growth hormone locus with a total growth of cattle is probably caused by differences of growth hormone circulation as a result of the growth hormone gene variation (Sutarno 2006). Study of gene polymorphisms of growth hormone has also been done on some Indonesian local cattle such as Pesisir cattle (Jakaria et al 2007), Bali cattle (Jakaria et al 2009;Jakaria and Noor 2011), Madura cattle (Purwoko et al 2003;Hartatik et al 2013), PO cattle (Sutarno et al 2005;Sutarno 2010;Paputungan et al 2013;Rahayu et al 2014), Sumba Ongole cattle (Anwar et al 2015), Aceh cattle (Putra et al 2013(Putra et al , 2014 and Grati dairy cattle (Maylinda 2011).…”
Section: Growth Hormone Genementioning
confidence: 99%